Nuclear radii from first principles - Miyagi, Takayuki (Frontiers in Physics, 2025)
With the combination of nuclear interactions from chiral effective field theory and various many-body techniques, one can perform systematically improvable ab initio calculations. As the improvable framework enables us to quantify the uncertainty, it is particularly useful to make a prediction for which performing experiments is difficult or even impossible. Neutron skin thickness, the difference between neutron and proton distribution radii, is a key quantity related to the properties of infinite nuclear matter. Since neutrons do not have a net electric charge, the neutron-distribution radius is difficult to measure, preventing precise measurement of neutron skin thickness. On the other hand, recent developments in laser spectroscopy techniques can provide detailed information on the charge distribution and opportunities for detailed comparisons to theoretical results. Testing the theoretical frameworks with the measurable charge radii should be a step toward predicting other quantities, such as neutron skin thickness. This contribution reviews recent advances in nuclear radii and neutron skin from ab initio calculations.